2017
DOI: 10.1017/s1751731117000234
|View full text |Cite
|
Sign up to set email alerts
|

Early kit mortality and growth in farmed mink are affected by litter size rather than nest climate

Abstract: We investigated the effects of nest box climate on early mink kit mortality and growth. We hypothesised that litters in warm nest boxes experience less hypothermia-induced mortality and higher growth rates during the 1st week of life. This study included data from 749, 1-year-old breeding dams with access to nesting materials. Kits were weighed on days 1 and 7, dead kits were collected daily from birth until day 7 after birth, and nest climate was measured continuously from days 1 to 6. We tested the influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…However, they reported positive significant genetic correlations between number of live born kits with survival rate at day 7 (0.42) and between number of weaned kits with survival rate at 6 mo (0.65). Schou and Malmkvist (2017) indicated that total number of living kits was significantly (P < 0.001) negatively associated with kits mortality rates (slope = −0.25), whereas the total number of born kits had a significant (P < 0.001) positive influence on kit mortality rates (slope = 0.24) in farmed mink. Furthermore, Lagerkvist et al (1994) observed that selection for litter size at week 3 resulted in a reduced genetic trend for kit mortality in mink, which was in agreement with our results.…”
Section: Genetic Correlations Between Survival Rate and Litter Size Tmentioning
confidence: 97%
See 1 more Smart Citation
“…However, they reported positive significant genetic correlations between number of live born kits with survival rate at day 7 (0.42) and between number of weaned kits with survival rate at 6 mo (0.65). Schou and Malmkvist (2017) indicated that total number of living kits was significantly (P < 0.001) negatively associated with kits mortality rates (slope = −0.25), whereas the total number of born kits had a significant (P < 0.001) positive influence on kit mortality rates (slope = 0.24) in farmed mink. Furthermore, Lagerkvist et al (1994) observed that selection for litter size at week 3 resulted in a reduced genetic trend for kit mortality in mink, which was in agreement with our results.…”
Section: Genetic Correlations Between Survival Rate and Litter Size Tmentioning
confidence: 97%
“…However, this low estimate can be due to adjusting the mortality rate for number of live born kits in their study. Moreover, Schou and Malmkvist (2017) indicated that total number of kits born was positively correlated with higher risks of kit death and reduced growth rate in farmed mink (P < 0.001). In addition, studies on commercial pig breeds indicated that despite the considerable genetic improvement obtained for litter size at birth during the past decades, preweaning piglet mortality has been relatively high (Su et al, 2007;Hellbrügge et al, 2008).…”
Section: Genetic Correlations Between Survival Rate and Litter Size Tmentioning
confidence: 99%
“…By linear regression analysis, decreased feed energy intake per female in week 17 (23 rd to 29 th of April) (p = 0.031) and increased feed energy intake per female and litter in week 24 (11 th to 17 th of June) were significantly associated with a reduction in prevalence of MUTD (p = 0.049). No associations (p > 0.05) were found between feed energy consumed and prevalence of MUTD in any of the remaining weeks investigated (w. [15][16][17][18][19][20][21][22][23][24][25][26]. Results are displayed in table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Housing was according to legislation and standards for mink production in Denmark. The commercial standard-production cage system used in Denmark at the time of this study, have been previously described [16]. Each cage was additionally equipped with an elevated platform (a shelf) and a moveable soft plastic tube, according to Danish regulations for the keeping of mink.…”
Section: Study Design and Farmsmentioning
confidence: 99%
“…The survival rate of the young is determined by many factors, including color variety, age of the mother, and litter size Kołodziejczyk 2006, Kołodziejczyk andSocha 2012]. Schou and Malmkvist [2017] and Seremak et al [2013] found that litters that were too numerous had a higher mortality rate than litters that were less numerous, which was due to the fact that pups in larger litters (more than 9 young) are much smaller and the mother has limited feeding capacity. Due to the fact that mink are born naked, blind and deaf, weighing about 9-12 grams, especially during the early stages of mink rearing, maintaining an adequate nest temperature is a problem, as mink do not have a developed thermoregulatory mechanism and are prone to rapid hypothermia due to their relatively large body surface area relative to volume [Brown and Lasiewski 1972, Harri et al 1991, Castella and Malmkvist 2008.…”
Section: Introductionmentioning
confidence: 99%